2016
DOI: 10.4149/gpb_2015041
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective potential of zingerone against nonalcoholic fatty liver disease in rats fed with fructose-enriched diet

Abstract: Overconsumption of fructose increases the risk of nonalcoholic fatty liver disease (NAFLD), obesity and metabolic syndrome. NAFLD is currently one of the most common etiologies of chronic liver disease worldwide. The aim of the present study is to evaluate the hepatoprotective potential of zingerone against fructose-enriched diet-induced rat model of nonalcoholic fatty liver disease. Male albino Wistar rats were used and randomly divided into four groups: group 1, control rats fed with standard pellet; group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…3). This is in agreement with the findings of Narayanan and Jesudoss (2016) in which administration of zingerone was found to improve the lipid profile in rats fed with fructose enriched diet.…”
Section: Discussionsupporting
confidence: 93%
“…3). This is in agreement with the findings of Narayanan and Jesudoss (2016) in which administration of zingerone was found to improve the lipid profile in rats fed with fructose enriched diet.…”
Section: Discussionsupporting
confidence: 93%
“…In line with this, previous researchers demonstrated that ginger positively modulated the antioxidant status of testis [12]. Narayanan and Jesudoss [57] considered ginger as one of the natural alternatives for the prevention of hyperlipidemia. A possible explanation for its antihypertriglyceridemic effect was provided by Platel and Srinivasan [59] who recorded that ginger, when added to animal diet, produces a considerable increase in pancreatic and intestinal lipase that plays a vital role in fat digestion.…”
Section: Discussionsupporting
confidence: 55%
“…3 C). 81 , 82 , 83 , 84 , 85 , 86 All the Chinese medicines in Fig. 3 C reduced blood glucose levels.…”
Section: Chinese Herbs and Fatty Liver Diseasementioning
confidence: 91%